Leptin promotes epithelial-mesenchymal transition of breast cancer via the upregulation of pyruvate kinase M2 - Wei, Lan (J Exp Clin Cancer Res, 2016)
BACKGROUND: Accumulating researches have shown that epithelial-mesenchymal transition (EMT) contributes to tumor metastasis. Leptin, a key adipokine secreted from adipocytes, shapes the tumor microenvironment, potentiates the migration of breast cancer cells and angiogenesis, and is also involved in EMT. However, the potential mechanism remains unknown. This study aims to explore the effect of leptin on EMT in breast cancer cells and the underlying mechanism. METHODS: With the assessment of EMT-associated marker expression in MCF-7, SK-BR-3, and MDA-MB-468 cells, the effect of leptin on breast cancer cells was analyzed. Besides, an array of pathway inhibitors as well as RNA interference targeting pyruvate kinase M2 (PKM2) were used to clarify the underlying mechanism of leptin-mediated EMT in vitro and in vivo. RESULTS: The results demonstrated that leptin promoted breast cancer cells EMT, visibly activated the PI3K/AKT signaling pathway, and upregulated PKM2 expression. An antibody against the leptin receptor (anti-ObR) and the PI3K/AKT signaling pathway inhibitor LY294002 significantly abolished leptin-induced PKM2 expression and EMT-associated marker expression. SiRNA targeting PKM2 partially abolished leptin-induced migration, invasion, and EMT-associated marker expression. In vivo xenograft experiments indicated that RNA interference against PKM2 suppressed breast cancer growth and metastasis. CONCLUSIONS: Our data suggest that leptin promotes EMT in breast cancer cells via the upregulation of PKM2 expression as well as activation of PI3K/AKT signaling pathway, and PKM2 might be one of the key points and potential targets for breast cancer therapy.